Chronicle of Processes Leading to the 2018 Eruption at Mt. Etna As Inferred by Seismic Ambient Noise Along With Geophysical and Geochemical Observables. Issue 10 (21st October 2022) - Büyükakpınar, Pınar; Cannata, Andrea; Cannavò, Flavio; Carbone, Daniele; De Plaen, Raphael S. M.; Di Grazia, Giuseppe; King, Thomas; Lecocq, Thomas; Liuzzo, Marco; Salerno, Giuseppe
Abstract: This work analyzes temporal variations of seismic velocities at Mt. Etna from August 2018 to February 2019. During this time period, a strong flank eruption accompanied by intense seismicity and ground deformation took place along a fracture that opened on 24 December 2018 at the base of the New South‐East summit crater. Furthermore, two moderate earthquakes—the 6 October 2018 M L 4.7 and 26 December 2018 M L 4.8—associated with the volcanic activity were recorded. In this study, we computed cross‐correlation functions (CCFs) between windows of seismic ambient noise to identify seismic velocity variations within the volcano edifice. We calculated daily CCFs at 16 stations for 120 interstation pairs using the vertical component in the 1.0–1.5 Hz frequency band. We observe that dv/v starts to decrease rapidly from the beginning of October 2018 and reaches approximately −0.45% in the pre‐eruption period. The spatio‐temporal distribution of seismic velocities shows that the reduction of dv/v mostly occurs in the vicinity of the summit and close to the flank area and is interpreted to be affected by magmatic intrusion at 0–3 km depth. To infer the source mechanism of this eruption, we compared these observations with volcano‐tectonic earthquakes, volcanic tremor, volcanic degassing, gravity, and ground deformation data. Our study suggests that a relationship between magma intrusion and associated crack opening is responsible for the decrease of dv/v . Plain Language Summary: Seismic ambient noise offers a powerful method to monitor variations of seismic wave velocities due to volcanic and seismic activities. In this study, we investigated the magma intrusion before the 24 December 2018 Mt. Etna flank eruption. Due to the large number of permanent seismic stations in our study region, we retrieved a large data set to calculate the seismic velocity changes between August 2018 and February 2019. An unprecedented seismic swarm in the instrumental period occurred at the same time as the aforementioned volcanic activity. We found a drastic reduction in the seismic velocities in the pre‐eruption period. We inferred this decrease is due to the opening of cracks caused by the intrusion of magma following significant stress changes in the crust. For the first time, we compared the seismic ambient noise analysis results with geophysical and gas geochemical parameters in the study region. The multi‐comparison of different parameters also supports our results. It is proposed that the seismic ambient noise analysis will be implemented in real‐time to monitor and detect possible precursor changes associated with the uprise of magma batches at Mt. Etna. Key Points: Seismic velocities display a reduction trend by −0.45% preceding the 2018 Mt. Etna eruption Multi‐parameter analysis shows a relationship between magma intrusion and the drop in seismic velocities Seismic velocity changes from ambient noise can be used in monitoring Mt. Etna for possible eruption precursors